HUBUNGAN VENTILASI DAN KEPADATAN HUNIAN DENGAN PENULARAN SILANG TBC PARU DALAM KELUARGA - Kustin; Harianah Akib (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2018)
TB disease is often associated with a slum environment. People who live in densely populated and poorly ventilated conditions are most likely to be infected. Environmental factors that can affect the incidence of pulmonary TB include ventilation in the room, humidity, temperature, lighting, type of floor, and the act of opening a window. The purpose of this study was to determine the relationship of ventilation and occupancy density with cross transmission of pulmonary tuberculosis in the family. This research is presented in the form of quantitative research with a correlational research design. While the approach used in this research is Cross Sectional. The population in this study was 60 respondents with a sample of 53 respondents. The sampling technique used in this study is total sampling. The results of the bivariate analysis with the Lambda test obtained a value of 0.003 <0.05 ie there is a relationship between ventilation and cross-transmission of pulmonary tuberculosis in the family. And also obtained a value of 0.001 <0.05, namely there is a relationship of residential density with the transmission of pulmonary tuberculosis in the family. The conclusion of this study is that if ventilation that does not meet the requirements is likely to not occur cross-pulmonary TB transmission in the family, while ventilation that meets the requirements can occur cross-pulmonary TB transmission in the family. If the density of occupancy does not meet the requirements, it is possible that there is no cross-transmission of pulmonary tuberculosis in the family, while occupancy density that occurs may occur cross-transmission of pulmonary TB in the family